Kemandirian Siswa Dalam Pembelajaran PAI DI SDN 28 Koto Nan IV Air Batu Kenagarian Pelangai Kabupaten Pesisir Selatan - Maha Suci; Irna Andriati; Zulfani Sesmiarni; Arifmiboy (Program Studi Akuntansi IKOPIN, 2022)
This research was motivated by the lack of independence of students in learning PAI such as not daring to ask or answer questions from the teacher, not believing in doing assignments, cheating on their friends and making noise in class when there was no teacher. So the formulation of this research is what causes the lack of student independence in terms of confidence and responsibility in PAI learning in class V at SDN 28 Koto Nan IV Air Batu. The purpose of this study was to determine the cause of the low independence of students in terms of confidence and responsibility in PAI learning in class V at SDN 28 Koto Nan IV Air Batu Kenagarian Pelangai Pesisir Selatan Regency. This type of research is descriptive research, namely research conducted to describe or explain in a systematic, factual and accurate manner about the facts and characteristics of a particular population. This research was conducted at SDN 28 Koto Nan IV Air Batu Kenagarian Pelangai, Pesisir Selatan Regency. The key informants of this study were fifth grade students who were less independent with supporting informants, namely Islamic religious education teachers who taught in fifth grade. Data collection techniques were observation and interviews. Based on the results of the study, it was found that the cause of the lack of independence of fifth grade students in terms of self-confidence and responsibility in learning Islamic Religious Education was due to the factors of parents who were busy working, did not pay attention and did not guide their children and the factor of teachers who did not care about students with low abilities.